2021
DOI: 10.1097/hjh.0000000000002864
|View full text |Cite
|
Sign up to set email alerts
|

Genetically determined hypertensive phenotype affects gut microbiota composition, but not vice versa

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 45 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…Intercaecal administration of investigated compounds and the collection of samples requires surgical preparation [39,40] and potential use of antibiotics that might significantly affect microbial data. Due to this fact, the colon is more frequently used for the evaluation of microbial communities and their impact on health in mammals [41,42]. The gut lumen is separated from the circulation by layers of tissues, which altogether form the gut-blood barrier (GBB).…”
Section: Gut-blood Barrier (Gbb) and Microbiotamentioning
confidence: 99%
“…Intercaecal administration of investigated compounds and the collection of samples requires surgical preparation [39,40] and potential use of antibiotics that might significantly affect microbial data. Due to this fact, the colon is more frequently used for the evaluation of microbial communities and their impact on health in mammals [41,42]. The gut lumen is separated from the circulation by layers of tissues, which altogether form the gut-blood barrier (GBB).…”
Section: Gut-blood Barrier (Gbb) and Microbiotamentioning
confidence: 99%
“…Gut microbiota-derived molecules may affect cardiovascular homeostasis acting directly on the blood vessels and the heart (31,32). Reciprocally, changes in the cardiovascular system may affect gut microbiota by altering the structure and function of bacterial habitat, i.e., intestines (33). It has been found that gut bacteria may affect the circulatory system indirectly by modulating gut sympathetic activity (34) and RAS.…”
Section: Ras and Gut Microbiota In Health And Disease Cardiovascular Systemmentioning
confidence: 99%
“…It is important to note that the complexity of the microbiota can produce unexpected results such as increased BP in Dahl salt‐sensitive rats receiving fecal transplants from salt‐resistant normotensive rats 9 . A recent study on inter‐strain fecal transplant in rats showed no effect on BP and did not produce long‐term changes in gut bacteria composition 130 …”
Section: Treatment Of Hypertension Based On Gut Microbesmentioning
confidence: 99%
“…9 A recent study on inter-strain fecal transplant in rats showed no effect on BP and did not produce long-term changes in gut bacteria composition. 130…”
Section: Fmtmentioning
confidence: 99%